Insights into patient preferences for elective surgery during the COVID-19 pandemic. (April 2021) - Hotchen, A. J.; Khan, S. A.; Khan, M. A.; Seah, M.; Charface, Z. H.; Khan, Z.; Khan, W.; Kang, N.; Melton, J. T. K.; McCaskie, A. W.; McDonnell, S. M.
No abstract available